Existence of Multiple Matchmakers in a Two-sided Matching Market. (June 2016) - Ramani, Vinay
This article studies a two-sided matching market with intermediation where an incumbent match-maker faces the threat of entry from a potential entrant. When the payoff from matching is complementary in the types of the agents, there exists a weak sequential equilibrium, either with entry and market segmentation or with entry deterrence. When intermediation is costless, allowing for sequential entry yields the socially efficient outcome as the number of entrants tends to infinity. Introducing intermediation costs leads to a welfare loss.